The differences in microbial composition may be an important cause of pancreatic pseudocyst infection—an observational study based on 16SrRNA - Li, Yaoting; Zhao, Yongzhan; Hou, Senlin; Zhang, Lichao (Frontiers in Microbiology, 2025)
BackgroundThere are no studies of pancreatic pseudocyst infections related to microorganisms. The purpose of this study was to analyze the microbiological differences between infective and non-infective pseudocysts.MethodsThis was an observational cohort study. Thirty-seven patients with pancreatic pseudocyst who underwent EUS drainage at our center were included in the study. According to postoperative infection, the patients were divided into infected group and non-infected group. Capsular fluid was collected during endoscopic drainage and microbial sequencing was performed.ResultsThe clinical features of the two groups were similar (p > 0.05). There was no significant difference in α diversity between infected and non-infected groups (p > 0.05). There was significant difference in β diversity between infected and uninfected groups (Adonis, R2 = 0.039, p = 0.019). Random forest maps identified the top five species with the greatest abundance differences. At the genus level, the relative abundance of Klebsiella, Streptococcus, Collinsella, Phascolarctobacterium, and Megamonas in the sac fluid of infected group was significantly higher than that of non-infected group.ConclusionThe differences in the microbial composition of the cyst fluid in pancreatic pseudocyst may have an impact on postoperative infections. The relative abundance of Klebsiella, Streptococcus, Collinsella, Phascolarctobacterium, and Megamonas in infected group was significantly higher than that in noninfected group. Further research is still needed in the future to confirm this.